Nucleophilic Addition to N-Vinylpyridiniums by Using Ion-Pair Extraction with Tetracyanocyclopentadienides - Sakai, Takeo; Kitamura, Takumi; Yokoe, Shunya; Uemura, Mayu; Mori, Yuji (Synthesis, 2025)
N-Vinylpyridinium is a useful electrophilic species in synthetic organic chemistry. In this study, we reinvestigated the addition reaction of N-vinylpyridinium, which has received limited attention in the past several decades. The reaction conditions were screened in detail with the aid of tetracyanocyclopentadienide (TCCP) ion-pair extraction and its extraction prediction equation, and the optimal reaction conditions were identified to entail the use of 2,2,2-trifluoroethanol (TFE) as an additive and dichloromethane as solvent. We successfully obtained 14 addition products with various substitution patterns, among which 3,5-dimethyl-N-vinylpyridinium provided the addition product in up to 85% yield. The reduction of the pyridinium core advanced smoothly, indicating that the TCCP anions did not significantly influence the reactivity of the platinum-catalyzed hydrogenation.
Keywords: ion-pair extraction; addition; pyridinium; tetracyanocyclopentadienide; nitrogen heterocycle